2020
DOI: 10.1186/s12864-020-6459-6
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic and proteomic atlas of expression in the Nezara viridula (Heteroptera: Pentatomidae) midgut suggests the compartmentalization of xenobiotic metabolism and nutrient digestion

Abstract: Background: Stink bugs are an emerging threat to crop security in many parts of the globe, but there are few genetic resources available to study their physiology at a molecular level. This is especially true for tissues such as the midgut, which forms the barrier between ingested material and the inside of the body. Results: Here, we focus on the midgut of the southern green stink bug Nezara viridula and use both transcriptomic and proteomic approaches to create an atlas of expression along the four compartme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…GO term overrepresentation analysis (Table S6) showed that genes commonly overexpressed in the midgut of all larval stages are related to digestive functions such as lipid metabolism (GO:0006629) and proteolysis (GO:0006508). This finding was also observed in the stink bug N. viridula, and is commonplace among insects as it has been proven that they play an important role in the breakdown of proteins in the ingested food [17,30,31].…”
Section: Comparisons Across Larval Stages Suggest Conserved Regulatio...supporting
confidence: 63%
See 2 more Smart Citations
“…GO term overrepresentation analysis (Table S6) showed that genes commonly overexpressed in the midgut of all larval stages are related to digestive functions such as lipid metabolism (GO:0006629) and proteolysis (GO:0006508). This finding was also observed in the stink bug N. viridula, and is commonplace among insects as it has been proven that they play an important role in the breakdown of proteins in the ingested food [17,30,31].…”
Section: Comparisons Across Larval Stages Suggest Conserved Regulatio...supporting
confidence: 63%
“…For L2, L3, and L4 midguts, dissected samples were sent to the Centre for Proteomics (Antwerp, Belgium) for gel-free analysis as was described previously [ 17 ]. For spatial compartment analysis of artificial diet fed L5 samples, a gel-based approach was used at the Proteomics Facility of the Institute of Molecular Biology and Biotechnology (Heraklion, Greece).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the potential roles of hemipteran specific ABC-H transporters, we used RNAi to individually knock down the expression of several ABC-H genes in the stink bug N. viridula . Using previous transcriptomic information [ 47 ]⁠, it was observed that the ABC-H genes were expressed primarily in the M4 midgut region and non-gut tissue (Table S7 ). We selected 8 out of 14 genes for RNAi knockdown based on high expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the spatial-temporal expression pattern of each APC transporter in BPHs, the RNA-seq data at 15 developmental stages (egg-24 h, egg-48 h, egg-5 days, 1st-24 h, 1st-48 h, 2nd-24 h, 2nd-48 h, 3rd-24 h, 3rd-48 h, 4th-24 h, 4th-48 h, 5th-24 h, 5th-48 h, female adult-24 h, and female adult-72 h) and five tissues (head, salivary glands, integument, gut, and ovaries) were downloaded from the NCBI database (SRR13958477-SRR13958499) 11 . A pseudoalignment-based software, Kallisto v0.46.1, was used to quantify the transcript abundance in transcripts per million (TPM) counts for each identified gene ( Denecke et al, 2020 ; Sheng et al, 2021 ). After the expression data of all APC transporter genes were obtained, two heatmaps illustrating the expression profiles of each APC member at different developmental stages and different tissues of the BPH were generated using TBtools.…”
Section: Methodsmentioning
confidence: 99%